Family and COVID-19: alternative and complementary ways of caring (Research, Society and Development, 2023)
Introduction: The COVID-19 pandemic has been responsible for impacts in various areas globally, considered a public health emergency. It was observed that several changes were made in relation to health care, in the family and hospital context, with the aim of preventing or treating the disease. Objective: To analyze the alternative resources used to allopathy and describe the use of alternative and complementary forms of care in the fight against COVID-19. Methodology: This is a qualitative, descriptive and analytical study, through semi-structured interviews carried out in São Luís-MA, with individuals whose family member evolved to death from COVID-19 diagnosed through a positive result. Results: two categories were organized, namely: the use of medicinal plants and the search for the sacred. Although there are medications aimed at symptoms, the population also sought to use alternative treatments to obtain symptomatic relief and/or cure the disease. The most used product was tea, predominantly those rich in vitamin C, which can be prepared in different ways. Regarding sympathies, the study demonstrated that spirituality, as well as religiosity, were fundamental for the population, as they served as support and comfort for patients and also for their families. Conclusion: The search for and subsequent use of alternative and complementary ways of caring, either preventively or aiming at symptom relief and cure, has been an important additional mechanism for the population to be able to go through the pandemic period.